Physiological changes in the regulation of calcium and phosphorus utilization that occur after the onset of egg production in commercial laying hens - Garcia-Mejia, R. Alejandra; Sinclair-Black, Micaela; Blair, Lyssa R.; Angel, Roselina; Jaramillo, Bibiana; Regmi, Prafulla; Neupane, Nabin; Proszkowiec-Weglarz, Monika; Arbe, Xabier; Cavero, David; Ellestad, Laura E. (Frontiers in Physiology, 2024)
At the onset of egg production, physiological changes governing calcium and phosphorus utilization must occur to meet demands for medullary bone formation and eggshell mineralization. The objective of this study was to identify these changes and determine if they are influenced by dietary supplementation with 1α-hydroxycholecalciferol (AlphaD3™, Iluma Alliance). Commercial laying hens fed either a control or AlphaD3-supplemented diet beginning at 18 weeks of age were sampled at 18 (n=8) and 31 weeks (n=8/diet) to evaluate mRNA expression associated with calcium and phosphorus utilization in kidney, shell gland, ileum, and liver, circulating vitamin D3 metabolites, and bone quality parameters in humerus, tibia, and keel bone. Though diet did not heavily influence gene expression at 31 weeks, several significant differences were observed between 18- and 31-week-old hens. Heightened sensitivity to hormones regulating calcium and phosphorus homeostasis was observed at 31 weeks, indicated by increased parathyroid hormone receptor 1, calcium-sensing receptor, calcitonin receptor, and fibroblast growth factor 23 receptors in several tissues. Increased renal expression of 25-hydroxylase and vitamin D binding protein (DBP) at 31 weeks suggests kidney participates in local vitamin D3 25-hydroxylation and DBP synthesis after egg production begins. Biologically active 1,25(OH)2D3 was higher at 31 weeks, with correspondingly lower inactive 24,25(OH)2D3. Increased expression of plasma membrane calcium ATPase 1 and calbindin in kidney, shell gland, and ileum suggests these are key facilitators of calcium uptake. Elevated renal inorganic phosphorus transporter 1 and 2 and sodium-dependent phosphate transporter IIa at 31 weeks suggests increased phosphorus excretion following hyperphosphatemia due to bone breakdown for eggshell formation. Diet did influence bone quality parameters. Bone mineral density in both humerus and tibia was higher in AlphaD3-supplemented hens at 31 weeks. Tibial bone mineral content increased between 18 and 31 weeks, with AlphaD3-supplemented hens increasing more than control hens. Moreover, control hens exhibited diminished tibial breaking strength at 31 weeks compared to hens at 18 weeks, while AlphaD3-supplemented hens did not. Together, these results indicate supplementation with AlphaD3 enhanced bone mineralization during the medullary bone formation period and elucidate the adaptive pathways regulating calcium and phosphorus utilization after the onset of lay.